ANALISIS MINAT REPURCHASE PRODUK UNICORN TOKOPEDIA DITINJAU DARI INFORMASI PRODUK, ESTETIKA DAN SISTEM LAYANAN PADA KONSUMEN DI KOTA NGANJUK - Moelyono, Istan Wighara; Suwandi, Suwandi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to analyze consumer interest in the city of Nganjuk to repurchase / repurchase products in terms of (1) Product Information, (2) Aesthetics, and (3) Service System provided by the unicorn company Tokopedia. We used causal associative research, for data collection methods used online questionnaires. The number of population and samples from this study amounted to 250 respondents, namely consumers who have purchased products at the unicorn Tokopedia company with a time span between July to November 2021 in the city of Nganjuk. For sampling, we used purposive sampling technique. Hypothesis testing through t test (partial). This study analyzed the data using structural equation modeling (SEM) with the PLS 3.0 software package.